Lexical bundles: facilitating university "talk" in group discussions - Chan, Swee Heng; Kashiha, Hadi; Tan, Helen (Canadian Center of Science and Education, 2014)
Group discussion forms an integral language experience for most language learners, providing them with an opportunity to express themselves in a naturalistic setting. Multi-word expressions are commonly used and one of them is lexical bundles. Lexical bundles are types of extended collocations that occur more commonly than we expect; they are considered as building blocks in discourse and play a crucial role in creating textual consistency. They contribute to a better understanding of the meaning of particular contexts of language use as well as creating a flow and rhythm in the discourse. This paper investigated the frequency, structures and functions of lexical bundles in a corpus of group discussion of proficient nonnative university undergraduate students, to unravel the application of lexical bundles in managing the talk in group discussion. Results of the analysis showed that lexical bundles accounted for a remarkable proportion of students’ lexis in their group discussions; showing a variety of structures and functions that indicate a dexterous yet formulaic automaticity that characterize proficient language use, thus having implications for language learning and teaching.